Oridonin Sensitizes Cisplatin-Induced Apoptosis via AMPK/Akt/mTOR-Dependent Autophagosome Accumulation in A549 Cells - Yang, Huahong; Gao, Yun; Fan, Xiaoye; Liu, Xingkai; Peng, Liping; Ci, Xinxin (Frontiers in Oncology, 2019)
AMPK-mediated autophagy and Akt/mTOR pathways play important roles in current cancer treatments. Oridonin (Ori), an ent-kaurane diterpenoid isolated from Isodon rubescens, exerts extensive anti-tumor potential and controversial effects on autophagy. In this study, we investigated the effect of Ori on the autophagy, apoptosis, and AMPK/Akt/mTOR pathways and determined whether Ori was related to the increased cisplatin sensitivity observed in A549 cells. First, we found that Ori suppressed Akt/mTOR, Bcl2 and autophagy flux with enhanced levels of Atg3, P62 and LC3II, which was also shown as the accumulation of autophagosomes. AMPK and pro-apoptotic proteins (caspase3, Bax and PARP) were activated in Ori-treated cells. With the pretreatment of compound c (AMPK inhibitor), the activation of autophagosomes, apoptosis and the inhibition of Akt/mTOR pathways induced by Ori were all reversed. The Ori-activated apoptosis-related markers mentioned previously and the cell-killing effect were reduced by 3-MA (inhibitor of autophagosomes) treatment. Therefore, we hypothesized that the Ori-induced pro-apoptosis effect was mediated by AMPK/Akt/mTOR-dependent accumulation of impaired autophagosomes. Furthermore, Ori could increase the sensitivity of cisplatin through its increased cell-killing, autophagy-suppressing and apoptosis-inducing activities. In addition to sensitizing cisplatin, Ori also alleviated cisplatin-induced acute renal injury in vivo, manifested as depleted BUN, CRE, kidney index and weight loss compared to the cisplatin group. In summary, apart from its protective effect on cisplatin-induced nephrotoxicity, Ori enhanced cisplatin sensitivity via its pro-apoptosis activity mediated by AMPK/Akt/mTOR-dependent autophagosome activation, which may be a potential therapeutic target for non-small cell lung cancer. v